KARAKTERISTIK STRUKTUR DAN ALUR DALAM TEKS CERPEN KARYA SISWA KELAS XI SMA NEGERI 2 PAYAKUMBUH - Anggraini, Anita; Tressyalina, Tressyalina; Noveria, Ena (Universitas Negeri Padang, 2018)
ABSTRACT The purpose of this study isÂ (1) describe the characteristics of the structure that appears in the short story text ofÂ the students of class XI SMA Negeri 2 Payakumbuh, (2) describe the characteristics of the flow in the short story text of the students of class XI SMA Negeri 2 Payakumbuh. The data in this research are 33 short story text. The data source of this study is an internal official document in the form of a collection of short texts of class XI MIPA 1 of SMA Negeri 2 Payakumbuh collected and archived by Indonesian teachers in semester one of the 2017/2018 academic year. Data were collected using documentation study. The research findings are short stories by students of class XI SMA Negeri 2 Payakumbuh in general, built four structures, namely orientation, complications, evaluation, and resolution. Of the 33 text stories studied, only nine short stories that use abstract, while the koda is not used at all. The plot used in the short story text of students of grade XI SMA Negeri 2 Payakumbuh in general is a forward flow. Of 33 short stories written by students, 29 short stories use advanced grooves, 2 short stories using backward flow, and 2 short stories using mixed grooves.Â Kata kunci: struktur, teks cerpen, alur, karakteristik